2022
DOI: 10.7324/jabb.2023.110214
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and partial characterization of serine proteases from jellyfish of the Antarctic region

Abstract: The growing demand for industrial proteases and enzyme-containing products substantiates the search for costeffective sources of enzymes. The aim of current research was to find a one-step approach for the isolation of the fraction of serine proteases from the jellyfish of the Antarctic region. Given our data, ion-exchange chromatography on diethylaminoethyl-sepharose carboxymethyl-sepharose was ineffective, in contrast to affinity chromatography on benzamidine-sepharose. The isolated fraction consists of enzy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
(15 reference statements)
0
3
0
Order By: Relevance
“…In addition, Raksha et al. (2021) [24] determined an effective reduction in NO generation (upper to 33 %) by peptides isolated from Euphausia superba at 2 mg/ml.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Raksha et al. (2021) [24] determined an effective reduction in NO generation (upper to 33 %) by peptides isolated from Euphausia superba at 2 mg/ml.…”
Section: Resultsmentioning
confidence: 99%
“…[21,22] Yang et al (2019) [23] demonstrated that the collagen from Tegillarca granosa was capable of producing 50 % inhibition of the ABTS * + free radical in a concentration between 54.40-96.30 μg/ml. In addition, Raksha et al (2021) [24] determined an effective reduction in NO generation (upper to 33 %) by peptides isolated from Euphausia superba at 2 mg/ml. These peptides, in addition to their antioxidant activity, can also have a direct effect on wound healing by exhibiting antimicrobial activity; especially when the skin barrier is compromised, exposing the area to potential pathogenic microorganisms.…”
Section: Resultsmentioning
confidence: 99%
“…Plasmin an endogenous brinolytic protease also resolved into two protein bands on SDS-PAGE [32]. Serine proteases with brinolytic activity from jelly sh showed 30 and 45 kDa peptides on SDS PAGE and have been suggested as potential thrombolytic agent [33].…”
Section: Discussionmentioning
confidence: 99%